EFEKTIVITAS DAN RELEVANSI UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK TERHADAP PERKEMBANGAN TEKNOLOGI DALAM MASYARAKAT - Andrie Djatmiko, Andreas; Nuroini, Anisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advances in digital technology have drastically changed children’s patterns of social interaction while also giving rise to various new forms of crime. Phenomena such as cyberbullying, online sexual exploitation, online grooming, and the misuse of children’s personal data pose major challenges for Indonesia’s legal system in providing effective protection. This study aims to analyze the effectiveness and relevance of Law No. 35 of 2014 Amending Law No. 23 of 2002 on Child Protection in light of the dynamics of digital technology, as well as to identify the factors influencing its implementation. An empirical legal research method was used in this study through legislative, conceptual, and sociological approaches. Data were obtained through a literature review and analyzed qualitatively using Soerjono Soekanto’s theory of legal effectiveness. The research findings indicate that Law No. 35 of 2014 remains conceptually relevant in safeguarding children’s rights. However, its implementation has not kept pace with the rapid advancement of digital technology. The main obstacles identified include normative weaknesses in the substance of the law, gaps in implementation by law enforcement officials, and regulatory overlaps with the Law on Information and Electronic Transactions, the Law on Sexual Violence Crimes, and the Criminal Code. The effectiveness of this law is influenced by factors such as its substance, law enforcement, infrastructure, society, legal culture, and technological developments. Therefore, legal reform and regulatory harmonization are essential to ensure that child protection in the digital age is more responsive and effective.